Navigating academic acculturation among international students: Peer network, advising, and field-specific challenges in STEM and non-STEM fields - Zou, Yang; Fu, Shuang (Journal of International Students, 2025)
This study investigated academic acculturation among international STEM and non-STEM students at U.S. universities using a mixed-methods approach (20 interviews and institutional career data from 2019 to 2023). The findings reveal that STEM students navigate structured pathways under pressure from research, whereas non-STEM students encounter language barriers and difficulties with career alignment. This research underscores the importance of discipline-specific support systems, including tailored guidance, expanded peer networks, and career resources, to facilitate successful academic and professional transitions.